The traumatized body and the camera lens: Reading WATI in the context of female cinematography - Desyukra, Joyandi; Pauhrizi, Erik Muhammad; Warsana, Dedi (FBSB UNY, 2025)
This study investigates how cinematography, informed by the female gaze, functions as a medium for articulating women's trauma in the context of domestic violence, as exemplified by the short film WATI. The research utilizes a practice-based methodology, positioning the film creation process as the primary data source. The analysis centers on key still photographs, applying a descriptive-reflective approach to examine framing, lighting, blocking, and body gestures. Findings reveal that extended close-ups and asymmetrical framing foreground Wati’s body as a locus of internal experience, while low-key and underlighting accentuate the psychological dimensions of trauma. Restrictive domestic compositions and passive gestures, such as silent submission, subtly communicate resistance. The faint smile in the after-credit scene operates as a mask of trauma, inviting viewers to engage with the character’s internal wounds. Collectively, WATI advances the discourse on the female gaze by rejecting objectification and presenting the female body as a site of tension among wounds, resignation, and defiance.